Propriedades estruturais e eletrônicas de nanotubos de carbono, BN e híbridos BxCyNz: um estudo por primeiros princípios - Freitas, Aliliane Almeida de (2015)
In the present work, we use first-principles calculations based on density functional theory, as implemented in the SIESTA code, to investigate the changes in the structural and electronic properties of the carbon, BN, and hybrid BxCyNz nanotubes produced by one or two of the following mechanisms: doping with carbon atoms, the application of external electric fields, by flattening of the cross section, the encapsulation of a carbon nanowire or the adsorption of hydrogen atoms (hydrogenation). We start with the study of double-walled boron nitride nanotubes (DWBNNTs), zig-zag and armchair, doped with carbon atoms, with chiral vectors (8,0)@(16,0) and (5,5)@(10,10), respectively. Two types of doping were considered: one C atom substituting a B atom on the inner wall (IW) and one C atom substituting a N atom on the outer wall (OW), which we call of CB[IW]@CN[OW], and the opposite situation results in CN[IW]@CB[OW]. In this sense, we generate a (type-p semiconductor)@(type-n semiconductor) and a (type-n semiconductor)@(type-p semiconductor), where the resulting DWBNNTs can be thought of as p-n junctions. At the same time, we apply an external electric field, with magnitude of 0,3 V/Å, in different directions, namely, perpendicular (Ey), parallel (Ex), and antiparallel (Ex) to the line formed by the dopants. Thus, depending on the direction of the applied field, we observe an increase or decrease in the band gap energy between the defect levels (Eig), and such cases are related to the reverse and direct polarization of the p-n junction, respectively. Afterwards, we study the insertion of a carbon nanowire (CNW) inside a (10.0) zigzag carbon nanotube and inside a (10.0) zig-zag BN nanotube. Such systems were called CNW@SWCNT and CNW@SWBNNT, respectively. We produce the flattening of the nanotubes and verify the behavior of the atomic structure of the nanowire as the flattening of the nanotube increases. From the obtained results, it was possible to conclude that, for both CNW@SWCNT and CNW@SWBNNT, there is a critical distance dc (distance between the parallel planes of the flattened nanotubes (d)), with the value of 3.60 Å, so that we can summarize our findings as follows: in the case d > dc, the carbon nanowire does not undergo any deformation; and in the reverse case (d < dc), the carbon nanowire binds to the wall of the nanotube and undergoes deformations. Regarding the electronic properties, we verify that the encapsulation of the CNW inside the SWCNT and SWBNNT, produces a significant reduction of the band gap energy (Eg) of such systems. Moreover, we observe ABSTRACT viii the creation of Dirac points for some flattening ratios of the nanotubes. Finally, we carry out a study on the adsorption of hydrogen atoms (hydrogenation) on the surface of double-walled boron nitride nanotubes (DWBNNTs) and hybrid nanotubes of boron nitride and carbon (DW(BN)xCyNTs). Due to the fact that the nanotubes have two walls, we consider the following cases: (i) coverages of 2H, 4H, 8H, 12H, and 16H on the inner wall, (ii) coverages of 2H, 4H, 8H, 16H, and 32H on the outer wall, and (iii) coverages of 2H, 4H, 8H, 16H, and 32H on both walls. Curiously, we find that for all hydrogen coverages considered, a strong deformation occurs in the hydrogen regions, causing the cross section of the nanotubes take different polygonal shapes: ellipsoidal, rectangular, hexagonal or octahedral. For coverages of 16H and 32H only on the outer wall, we observe that some hydrogens desorbed from the wall forming isolated H2 molecules without preferential orientation. We verify that, in some cases, the bond angles between the B, N and H or C and H atoms exhibit characteristics of the sp3 hybridization. Regarding the structural stability, we verify that the adsorption of H atoms in DWBNCNTs is more favorable than in DWBNNTs. Moreover, we conclude that is possible to control the band gap energy of the nanotubes through the hydrogen coverage.